EFFECTS OF LANDFILL LEACHATE ON GROUNDWATER QUALITY OF UNGUWAN DOSA, KADUNA - A. Saminu; A Isma’il; IA Chukwujama; O.B.E Salau (Academy Journal of Science and Engineering, 2022)
An assessment of the groundwater quality at the Unguwan Dosa landfill in Kaduna, Nigeria was conducted to determine interactions between the landfill wastes and groundwater. Groundwater samples were collected from two locations within the landfill at a distance of 100m and 150m, and analyzed for water quality parameters and heavy metals. The results indicated that the concentrations of some metals (Cr, Fe, Cd, Mn, and Co) at ranges of 0.31 - 051, 1.0-1.20, 0.005 ,0.4 and 0.051 and other water quality parameters in some sampling locations were slightly above the World Health Organization (WHO) and the Nigerian Standard for Drinking Water Quality (NSDWQ) standard limits. Lead was also detected in the groundwater samples, though at concentrations within the standard limits. Conclusively, the Unguwan Dosa landfill has impaired groundwater quality, thereby, posing environmental and human health concerns to the people living in the environs.